Proto-Property in Literary and Artistic Works: Sixteenth-Century Papal Printing Privileges - Ginsberg, Jane C. (The Columbia Journal of Law & the Arts, 2013)
This Study endeavors to reconstruct the Vatican’s precursor system of copyright, and the author’s place in it, inferred from examination of over five hundred privileges and petitions and related documents—almost all unpublished—in the Vatican Secret Archives.